Extramammary Perianal Paget’s Disease - M.N. Al Hallak (Case Reports in Gastroenterology, 2009)
Perianal Paget’s disease is a rare malignancy. It is rarely isolated and often associated with an underlying adenocarcinoma. It usually presents with anal itchiness and discomfort and can be misdiagnosed as hemorrhoids. Once the diagnosis of perianal Paget’s disease is granted, extensive work-up to find an underlying primary malignancy is crucial. Surgery is the standard modality of treatment of extramammary Paget’s disease (EMPD) with recurrence rates of 44–60%. Other different treatment modalities including radiotherapy, laser therapy, topical and systemic chemotherapy and the new emerging, promising photodynamic therapy are in the field of study. A 76-year-old man was referred to our hospital with a one-year history of anal itchiness and intermittent rectal bleeding. Skin shave and punch biopsies from the perianal area were reported back as perianal Paget’s disease with no underlying adenocarcinoma. The immunohistochemical stains were positive for cytokeratin 7 but also positive for cytokeratin 20 and CEA which indicated the essentiality of extensive investigations to find a primary malignancy. Skin exam showed no primary source. The investigations were unable to find the primary malignancy. Given the results of immunohistochemical stains we recommended local perianal Paget’s disease resection. The intraoperative frozen section showed adenocarcinoma around the anal sphincter. Ten days later the patient underwent an abdominoperineal resection and the final pathology report showed extensive adenocarcinoma in three quadrants of the perianal area with focal involvement of the rectal mucosa. We recommended an adjuvant chemotherapy with FOLFOX following surgery given the bulkiness of the disease. We conclude that once perianal Paget’s disease is diagnosed, an extensive work-up should be done to find the underlying primary malignancy. Immunohistochemical stains are helpful in raising the suspicion of underlying primary malignancy. Finding an underlying primary malignancy in patients with EMPD is prompt to choose the treatment modality and estimate the prognosis.